Pandemonium and order: Suretyship, surveillance, and taxation in early nineteenth-century Istanbul - Turna, Nalan (CAMBRIDGE UNIV PRESS, 2008)
This article analyzes the practice of suretyship (kefalet), surveillance and taxation in early nineteenth-century Istanbul. it deals with how the practice of suretyship functioned to achieve social control; it provided shelter for some but at the same time marginalized others with little or no social status. This article also analyzes the extent to which the state maintained order through suretyship. In this way, it intends to capture where and how state and society interacted through social and state control mechanisms. To this end, this article takes into consideration two particular events, the Greek uprising of 1821 and the abolition of the Janissary Corps in 1826, and demonstrates a growing tendency towards impersonal relations in terms of governmental practices of surveillance. Briefly, it illustrates how suretyship changed over time and how a gradual transition took place from personal to impersonal relations as well as within governmental practices. Furthermore, this article provides examples of similar practices by focusing on an institutional development that involved the government systematically accumulating knowledge about the population. Finally, it explores taxation practices by the government in order to show how the pre-modern (contractual) and the modern (statutory) state were not substitutes for each other, but rather shaped each other.
Keywords: Istanbul; nineteenth century; suretyship (kefalet); surveillance; taxation; Area Studies; Social Sciences - Other Topics